Disorders/Differences of Sex Development (DSD) and Gender Dysphoria: The Need of a National Guideline for Malaysia - Zainuddin, Ani Amelia; Mokhtar, Rafidah Hanim; Muhammad Noor Choliq, Atikah; Zabidi, Taqwa; Mohd Shukor, Nuur Asyikin; Hanin Hamjah, Salasiah; Jalaludin, Muhammad Yazid (IIUM Medical Journal Malaysia, 2025)
Disorders/Differences of Sex Development (DSD) are congenital conditions characterized by atypical chromosomal, gonadal, or anatomical sex, affecting approximately 0.1–2% of the global population. A subset of individuals with DSD also experiences gender dysphoria (GD), a psychological distress arising from incongruence between assigned sex at birth and experienced gender. Misdiagnosis between GD and DSD remains a major concern, particularly in Muslim-majority contexts such as Malaysia, where socio-cultural, religious, and medical perspectives intersect. Many individuals with unrecognized DSD are mistakenly categorized as transgender, resulting in stigmatization, marginalization, and limited access to healthcare, education, and religious participation. Islamic jurisprudence introduces the concept of khuntha to describe sex ambiguity, which overlaps with some DSD cases but requires nuanced differentiation from mutasyabbih (gender imitation) and transgenderism. While classical scholars distinguished between khuntha wadhih (discernible) and khuntha mushkil (intractable), contemporary management demands multidisciplinary collaboration. Integrating medical expertise with Shariah rulings is essential to determine appropriate pathways, including gender assignment, surgical interventions, and psychosocial support. The absence of structured guidelines in Malaysia exacerbates clinical, ethical, and religious dilemmas in managing these complex cases. This paper argues for the urgent development of a national guideline that combines evidence-based medical protocols with Islamic jurisprudence, ensuring culturally competent and patient-centered care. Such a framework would harmonize the roles of endocrinologists, psychiatrists, psychologists, religious scholars, and community stakeholders, providing comprehensive management that upholds both health outcomes and spiritual well-being. Establishing this synergy positions Malaysia to pioneer an integrated model for DSD and GD management in Muslim societies.